Doing Excellent Social Research with Documents Practical Examples and Guidance for Qualitative Researchers - Grant, Aimee (Taylor & Francis, 2018)
In today's society we increasingly create and consume written content and images. This includes a range of sources, from social media posts to records held within organisations, and everything in between, including news articles, blogs, shopping lists and official government documents. Critically reading these 'documents' can help us to understand a huge amount about society. Doing Excellent Social Research with Documents includes guidance on how to 'read between the lines', and provides an overview of six research projects which use documents as data.